Teacher Professional Development: Approaches and Lessons from a Pilot Study in Ethiopia. Issue 1 (2nd January 2021) - Cho, Moon-Heum; Lim, Seongmi; Hwang, Hongseop
Abstract: Effective teacher professional development is the key to improving primary school teachers' ability to implement learner-centered education; however, guidance on building such professional development programs for teachers in Africa that accommodates local realities and cultures has rarely appeared in the literature. Reported in this study, a collaboration between a Korean primary teacher education institution and a science and technology higher education institution in central Ethiopia produced a professional development program for primary school teachers in Ethiopia using the instructional systems design model. A five-phase development process, namely analysis, design, development, implementation, and evaluation was used to develop and implement a total of 60 lessons presented in 30 videos. Teacher participants were highly satisfied with the results, reporting significant improvement in their self-efficacy about using learner-centered education approaches after completing the program. Lessons learned are provided for those seeking to expand professional development opportunities for teachers in Africa.